Efficient pathway-driven scyllo -inositol production from myo -inositol using thermophilic cells and mesophilic inositol dehydrogenases: a novel strategy for pathway control - Kurashiki, Ryota; Takahashi, Masahiro; Okumura, Yuta; Ono, Tatsuya; Endo, Hirofumi; Makino, Kohei; Fukui, Kaho; Yokoyama, Kyosuke; Ishikawa, Shu; Yoshida, Ken-ichi; Ohshiro, Takashi; Suzuki, Hirokazu (Applied and Environmental Microbiology, 2024)
Enzyme cocktails are commonly employed for cell-free chemical synthesis; however, their preparation involves cumbersome processes. This study affirms that mesophilic enzymes in thermophilic crude extracts can function as specific catalysts at moderate temperatures, akin to enzyme cocktails. The catalyst was prepared by permeabilizing cells without the need for concentration, extraction, or purification processes; hence, its preparation was considerably simpler compared with conventional methods for enzyme cocktails. This approach was employed to produce pure scyllo -inositol from an economical substrate. Notably, this marks the first large-scale preparation of pure scyllo -inositol, holding potential pharmaceutical significance as scyllo -inositol serves as a promising agent for certain diseases but is currently expensive. Moreover, this approach holds promise for application in pathway engineering within living cells. The envisioned pathway is designed without chromosomal modification and is simply regulated by switching culture temperatures. Consequently, this study introduces a novel platform for both whole-cell and cell-free synthetic systems.